A study on perception of teachers and students toward online classes in Dakshina Kannada and Udupi District. Issue 3 (29th October 2020) - Kulal, Abhinandan; Nayak, Anupama
Abstract : Purpose: The study aims at analyzing the perception of teachers and students about online classes. The work tries to explain the opinions of students as regards the impact of online courses, their comfortability in its usag, and the support received from teachers in online classes along with teachers' opinions on efficacy, teaching practice followed and training received for an online class. Design/methodology/approach: The analysis was carried out using the data collected through two separate structured questionnaires for students and teachers in Dakshina Kannada and Udupi District in Karnataka. Data were recorded in SPSS and analyzed by using descriptive statistics. Findings: The study reveals that students are comfortable with online classes and are getting enough support from teachers but they do not believe that online classes will replace traditional classroom teaching. It also finds that teachers are facing difficulties in conducting online classes due to a lack of proper training and development for doing online classes. Technical issues are the major problem for the effectiveness of the online classes. Practical implications: Most of the colleges think of implementing online classes in their courses. Hence, it becomes essential to obtain the opinions of participants of online classes before applying for it. This study may help colleges to get a general view of online classes among teachers and students. Originality/value: Internet and new technologies gained importance in all fields including the education sector which gave scope for online classes. In addition to this, the COVID pandemic worldwide has also added to the relevance of online classes. In this light, it is necessary to understand student–teacher perceptions regarding online classes.